AL-2024 ALAŞIMININ İLETKENLİĞİNE ISIL İŞLEMİN ETKİLERİNİN DENEYSEL OLARAK ARAŞTIRILMASI - GÜNER, GÖKHAN ŞERİF (Fırat Üniveristesi, 2018)
Bu çalışmada elektrik iletkenliğin Al – 2024 alaşımının iletkenliğine etkisi araştırılmıştır. Deneysel çalışmada farklı ısıl işlemler uygulanarak Al – 2024 malzemesinde iletkenliğin nasıl değiştiği gözlemlenmiştir. Malzemelerin bazıları farklı sıcaklıklarda ısıtılmıştır, bazıları ise aynı sıcaklıkta ısıtılıp farklı soğuma koşullarında soğutularak iletkenlikleri ölçülmüştür. İletkenlik ölçüm işleminden sonra malzemeler parlatma işlemi için soğuk bakalite alınmıştır. Soğuk bakalite alınan malzemeler zımparalanıp, dağlandıktan sonra mikro optik mikroskopta iç yapı fotoğrafları çekilmiştir.

In this study, the effect of electrical conductivity on the conductivity of Al - 2024 alloy was investigated. In the experimental work, it was observed how the conductivity changed in Al - 2024 material by applying different heat treatments. Some of the materials were heated at different temperatures and others were heated at the same temperature and cooled at different cooling conditions to measure their conductivity. After the conductivity measurement, cold bakalite is taken for the polishing process of the materials. The cold mounting materials received sanded, internal structure at the micro optical microscope photograph was taken after etched.
Experimental study on the effects of Al-2024 aluminum conductive heat treatment
Keywords: Metalurji Mühendisliği